PENINGKATAN MANAJEMEN SDM DAN PEMASARAN PRODUK UMKM KE ARAH DIGITALISASI DI DESA PONGKAI KOTO KAMPAR - Syurti Primadayani; Fauzan Azmi; Novit Hidayat; Dika Irawan; Nurhayati Nurhayati; Femitri Eka Putri (Komunitas Manajemen Kompetitif, 2026)
This community service program aims to improve human resource management (HRM) capabilities and product marketing of Micro, Small, and Medium Enterprises (MSMEs) towards digitalization in Desa Pongkai Koto Kampar. The main problems faced by MSME actors in the village include limited understanding of HR management, lack of utilization of digital technology, and product marketing that is still carried out conventionally. The implementation methods of the program were conducted through socialization, training, mentoring, and evaluation for MSME actors. The materials provided included effective HR management, digital marketing strategies, the use of social media, and the utilization of marketplaces as promotional and product sales media. The results of the program showed an increase in the knowledge and skills of MSME actors in managing their businesses more professionally and adaptively to technological developments. In addition, MSME actors began utilizing digital platforms to expand their product marketing reach, thereby increasing business competitiveness. Therefore, this program is expected to encourage sustainable digital transformation of MSMEs in Desa Pongkai Koto Kampar and support the improvement of the village community’s economy